Identity thief [videorecording (DVD)] - Gordon, Seth; Bateman, Jason; Favreau, Jon; Cho, John, 1972-; McCarthy, Melissa, 1969-; Peet, Amanda, 1972-; T. I., 1980-; Rodríguez, Génesis, 1987- (Universal Studios Home Entertainment, 2013)
Mild-mannered businessman Sandy Patterson travels from Denver to Miami to confront the deceptively harmless-looking woman who has been living it up after stealing Sandy's identity.